An arc multi-electrode pixel structure for improving the response speed of electrowetting displays - Lai, Shufa; Tian, Lixia; Shen, Shitao; Yuan, Dong; Tang, Biao (Frontiers in Physics, 2022)
Electrowetting display (EWD) is a new reflective display device with low power consumption and high contrast. To further improve the response speed of pixels, an arc multi-electrode pixel structure was proposed, and a three-dimensional EWD device model was established in this paper. According to the model, the influence of the arc multi-electrode pixel structure on response speed was simulated, and the influence of a driving sequence on oil movement inside pixels was analyzed. In addition, comparative experiments of single-electrode and arc multi-electrode for oil movement inside pixels were completed. Experimental results showed that the response time of the arc multi-electrode structure was 0.9 ms faster than the single-electrode structure in a pixel opening stage. In the pixel closing stage, the oil recovery time can be accelerated by applying a boosting voltage to the electrode corresponding to the oil accumulation area, which was 2.3 ms faster than that of the single-electrode structure.